Técnicas lúdicas para fomentar la autoestima en los estudiantes de séptimo año de la escuela de educación básica 18 de noviembre periodo 2018-2019. - Conde Cango, Andrea Carolina (2019)
The present research work called LUDIC TECHNIQUES TO PROMOTE SELF-ESTIMATE IN THE SEVENTH YEAR STUDENTS OF THE BASIC EDUCATION SCHOOL “NOVEMBER 18” PERIOD 2018-2019 had as a general objective to implement playful techniques to promote self-esteem in seventh year students the School of Basic Education "November 18", the research was descriptive, cross-sectional and pre-experimental design; The methods applied were: scientific, analytical-synthetic, deductive, inductive. All these methods fulfilled specific roles during the research process. The Coopersmith Self-Esteem Inventory was applied as an instrument, in a sample of 34 seventh year students. The results obtained (pre-test) show a very low level of self-esteem for these situations: 44.12%; in general self-esteem, 23.53%; in social self-esteem, with 35.29%; in self-esteem in the home, with 26.47%; in school self-esteem, and with 41.18%; in total self-esteem. After the intervention (post-test) the self-esteem level was: 11.76%; in general self-esteem, 2.94%; in social self-esteem, with 2.94%; in self-esteem at home, with 2.94%; in school self-esteem, and with 0%; in total self-esteem. It is concluded that the population investigated in a high percentage, after the application of the alternative proposal through the workshops, shows a significant change in the level of self-esteem of the students. So it can be concluded that the recreational techniques used boosted the students' self-esteem, I recommend that the directors of the institution continue with the application of the intervention proposal.